Effects of balance training with stroboscopic glasses on postural control in chronic ankle instability patients. (19th November 2021) - Lee, Hyunwook; Han, Seunguk; Page, Garritt; Bruening, Dustin A.; Seeley, Matthew K.; Hopkins, J. Ty
Abstract: Individuals with chronic ankle instability (CAI) are believed to rely more on visual information during postural control due to impaired proprioceptive function, which may increase the risk of injury when their vision is limited during sports activities. Objectives: To compare (1) the effects of balance training with and without stroboscopic glasses on postural control and (2) the effects of the training on visual reliance in patients with CAI. Design: A randomized controlled clinical trial. Methods: Twenty‐eight CAI patients were equally assigned to one of 2 groups: strobe or control group. The strobe group wore stroboscopic glasses during a 4‐week balance training. Static postural control, a single‐leg hop balance test calculated by Dynamic Postural Stability Index (DPSI), and the Y‐Balance test (YBT) were measured. During the tests, there were different visual conditions: eyes‐open (EO), eyes‐closed (EC), and strobe vision (SV). Romberg ratios were then calculated as SV/EO, and EC/EO and used for statistical analysis. Results: The strobe group showed a higher pretest‐posttest difference in velocity in the medial‐lateral direction and vertical stability index under SV compared with the control group ( p  < .05). The strobe group showed higher differences in EC/EO for velocity in the medial‐lateral and anterior‐posterior directions, and 95% confidence ellipse area ( p  < .05), and in SV/EO for velocity in the medial‐lateral, 95% confidence ellipse area, and YBT‐anterior direction ( p  < .05). Conclusion: The 4‐week balance training with stroboscopic glasses appeared to be effective in improving postural control and altering visual reliance in patients with CAI.